Da cláusula penal em contratos relacionais - Costa Neto, Moacyr da (2016)
The penalty clause is a tradition in contracts. In Brazil, there is a consolidated understanding of it as a device that replaces the proposed role of the obligation agreed upon by the compensation required, in case the partners do not meet their obligations. The penalty clause also focuses on the classification of the delay as a way to reinforce the fulfillment of the obligation. In both cases, control of the penalty established will be kept, in order to prevent what could be considered unfair enrichment by the lender. The problem is that the socioeconomic situation, increasingly complex, requires more flexible coordination models which may enable contractors to take care of their interests with freedom and in a responsible way. The possibility presently being discussed is based on the relational contracts, because a certain incommensurability in the equivalence of the exchanges planned for the future is typical of them, and depends fundamentally on the confidence that a party places upon the other. In this situation, failure to perform what has been agreed upon - understood as the prohibition to exploit vulnerabilities -, will make room for punition strictu sensu not connected to indemnification purposes. Such strategy aims to reinforce trust as an indispensable duty, and its objective is to keep the contractual relationship. From an economic perspective, the solution offered, that is, the use of the penalty clause, will be a tool for reducing the transactional costs.